Spatial distribution of land susceptibility to degradation and recomendation for its improvement: a case study in the upper Solo Sub-Watershed - T M Basuki; W W Wijaya; N Wahyuningrum (Journal of Degraded and Mining Lands Management, 2016)
Spatial distribution of land properties and its susceptibility to degradation is essential for watershed management planning. Therefore, a study was carried out to assess spatial distribution of land susceptibity to degradation and provide some recommendations for its improvement. The location of the study was in the upper Solo sub-watershed which majority located in Central Java Province.  To classify degree of land susceptibility, a watershed typhology was applied. The typhology of watershed was based on land system and land cover type. Data of land cover and  slope steepness were derived from sattelite images. Land system was obtained from  Regional Physical Planning Programme for Transmigration (RePPProT). The results show that 36% of the study area is covered by highly susceptible and  55%  moderate susceptible to degradation. The rest are classified as very high, low, and very low suceptible to degradation. Improvement of the degraded land can be achieved by applying land use planning which is suitable with its capability, in fact agricultural areas are found at land use capability classes VI and VII which have to use for production forest and limited production forest. In addition, conservation practices need to be applied, especially for agricultural land at Vst of land capability class.